Punching shear strengthening of RC slabs using L-CFRP laminates. (1st September 2019) - Saleh, Haifa; Kalfat, Robin; Abdouka, Kamiran; Al-Mahaidi, Riadh
Highlights: L-CFRP laminates can significantly improve the punching shear capacity of RC slabs. Ductility of the strengthened slabs with L-CFRP laminate improved significantly. L-CFRP shifted the punching shear crack outside the strengthened zone. Abstract: This paper evaluates the behaviour of reinforced concrete (RC) slabs strengthened in shear with prefabricated L-shaped carbon fibre–reinforced polymer (CFRP) laminates. Four large scale slabs were tested; one slab was kept without strengthening and the other three slabs were strengthened with L-CFRP laminates using different configurations. The behaviour of the slabs strengthened with L-CFRP laminates was compared with that of a similar slab without shear reinforcement. The details of the strengthening methods implemented in the study, experimental setup and parameters of all the material used are provided. The experimental results are presented including deflection, strain readings and rotation as well as the crack pattern of each specimen. The test results reveal that using post installed L-CFRP laminates can significantly improve the punching shear capacity and deformation capacity of RC slabs. Further, the strengthening technique can also be used to prevent sudden collapse of buildings after punching shear failure by increasing the post punching deformation of slabs. The experimental results were compared with the theoretical results predicted by ACI 318 (2011), Eurocode 2 (2004) and Fib Model Code (2010).